Nonlinear amplification model in RC frame structures: Case study for Chi-Chi earthquake - Agrahari R.K.; Pathak K.K. (My University, 2025)
For the seismic design of non-structural components (NSCs), more awareness is required not only for prevention of catastrophic impact of human life but also for saving the economical crises. Due to the seismic ground motion, an inertia force acts upon the primary structure as well as non-structural components. The inertia force which affects the NSCs is related to the acceleration amplification factor. Various researchers presented the amplification factor as a function of the normalized height of the structures, but it is found that the amplification factor depends on other factors as well. In this paper, non-linear acceleration amplification models are proposed, which not only depends on the normalized height of the structure but also on the range of ground acceleration and the natural period of the structures. For this, five moments resisting RC frame models of 2,4,6,8 and 10 storeys are considered. A large number of ground motion data, having the range of less than 0.067g, twenty-nine ground motion data in the range of 0.067g to 0.2g and twenty-four ground motion data in the range of 0.2g to 0.3g respectively are accounted. Linear time history method is used for the analysis of all models. Based on the results, the non-linear amplification model is proposed and compared with the previously reported models. © 2021 by authors, all rights reserved.